2011
DOI: 10.1098/rspb.2011.1922
|View full text |Cite
|
Sign up to set email alerts
|

High dispersal ability inhibits speciation in a continental radiation of passerine birds

Abstract: Dispersal can stimulate speciation by facilitating geographical expansion across barriers or inhibit speciation by maintaining gene flow among populations. Therefore, the relationship between dispersal ability and speciation rates can be positive or negative. Furthermore, an 'intermediate dispersal' model that combines positive and negative effects predicts a unimodal relationship between dispersal and diversification. Because both dispersal ability and speciation rates are difficult to quantify, empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
425
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 305 publications
(474 citation statements)
references
References 62 publications
31
425
2
1
Order By: Relevance
“…HWI is related to wing aspect/ratio, an important metric in flight performance [26,49]. Wings with high aspect ratio/high HWI are longer, narrower and produce greater lift than wings with low aspect ratio/low HWI.…”
Section: (C) Comparative Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…HWI is related to wing aspect/ratio, an important metric in flight performance [26,49]. Wings with high aspect ratio/high HWI are longer, narrower and produce greater lift than wings with low aspect ratio/low HWI.…”
Section: (C) Comparative Analysesmentioning
confidence: 99%
“…Wings with high aspect ratio/high HWI are longer, narrower and produce greater lift than wings with low aspect ratio/low HWI. HWI correlates strongly with dispersal capabilities [49][50][51]. We calculated mean HWI for phasianoids and outgroups based on measurements from traditional museum skins with the wings prepared folded on the body.…”
Section: (C) Comparative Analysesmentioning
confidence: 99%
“…Recent studies of birds have found negative, positive and unimodal relationships between dispersal and diversification. For example, in the continental radiation of the Furnariidae, a diverse family of suboscine passerines from the Neotropics, there is a predominantly negative relationship between dispersal ability, as inferred from wing shape, and speciation rates estimated using a calibrated phylogeny [12]. By contrast, a macroevolutionary analysis of all bird families recovered a positive relationship between diversification rates and an index of dispersal propensity based on ecological characteristics [14].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the varied findings across studies may reflect real differences in the relationship between dispersal and diversification. In particular, the degree of discontinuity of the geographical setting may determine the relationship between dispersal and speciation rate [12]. Within continents, dispersal may have a predominantly negative effect because even poor dispersers can colonize remote areas, and increased dispersal results in elevated levels of gene flow across weak or moderate barriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation